2014
DOI: 10.18251/ijme.v16i2.904
|View full text |Cite
|
Sign up to set email alerts
|

A Woman’s Place: Women of Colour Navigating Doctoral Education in South Africa (pp. 15-35)

Abstract: The purpose of this study was to investigate the experiences of women of colour in South African doctoral education programmes. Through qualitative interviews with African, Indian, and Coloured female doctoral students, this study illuminates the challenges women of colour doctoral students face in progressing through doctoral education in South Africa, and the supports they utilize to help them persist and complete doctoral degrees. While the primary goals of recent efforts towards higher education transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…CRT is generous in facilitating an understanding of how students balance their experiences of persistence with stories of resilience and success. For instance, in an examination of the South African doctoral student experience, C. R. Snyder (2014) draws on the work of Ladson-Billings (1999) and Crenshaw (1991) to identify strategies for navigating expectations that challenge gender roles and identity for women of color.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…CRT is generous in facilitating an understanding of how students balance their experiences of persistence with stories of resilience and success. For instance, in an examination of the South African doctoral student experience, C. R. Snyder (2014) draws on the work of Ladson-Billings (1999) and Crenshaw (1991) to identify strategies for navigating expectations that challenge gender roles and identity for women of color.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Research regarding observations of psycho-social issues at the doctoral level is at the center of many institutional diversity efforts and is the goal of transforming academic environments away from historic legacies of exclusion towards environments that are more inclusive. For instance, C. R. Snyder (2014) cites Hurtado, Milem, Clayton-Pedersen and Allen (1999) in an examination of women of color in South African doctoral programs. She considers four areas where historically marginalized students face barriers to degree completion: challenging race and gender roles, balancing multiple roles, managing financial concern and access to resources, and finding support.…”
Section: Psychosocial Dimensions Related To Th E Doctoral Experiencementioning
confidence: 99%
“…Based on the results of Supardan's study (2009), it was concluded that multicultural-based learning has a significant influence on inter-ethnic interaction in national integration and shows a significant degree of sense of national solidarity. There is a study conducted by Snyder (2015) aims at researching the experiences of colored women in South Africa who are studying on a doctoral program. The study concludes that the institution condition where they study can support women of color to get a doctoral degree.…”
Section: Introductionmentioning
confidence: 99%
“…From the study on the experiences of women of colour in South African doctoral education programs, it can be concluded that the condition of the institution where they study can support in obtaining doctoral degree (Snyder, 2014). The study in an urban school in the United States, with a large number of students and various communities, concluded that there is educational improvement for the minor communities with good academic achievement (Wu, 2014).…”
Section: Introductionmentioning
confidence: 99%